Adalimumab induced psoriasis in a Crohn’s disease patient: a case report - Dhaifallah Alrakawi Alenizi (Journal of the Pakistan Medical Association, 2024)
Adalimumab is a human monoclonal antibody that selectively targets tumour necrosis factor-alpha (TNF- Alpha), a cytokine involved in the pathogenesis of various inflammatory and autoimmune disorders. Adalimumab has been approved worldwide for the treatment of several chronic immune-mediated diseases, including rheumatoid arthritis, psoriasis, psoriatic arthritis, ankylosing spondylitis, Crohn’s disease, ulcerative colitis, and juvenile idiopathic arthritis. One of the adverse reactions caused by Adalimumab is psoriasis. This study reports the case of a 37-year-old male with palmoplantar psoriasis triggered by adalimumab for treatment of Crohn’s disease. This eruption resisted complete clearance with various potent corticosteroids. The patient was referred back to the treating rheumatologist to possibly change adalimumab to another type of therapy. Keywords: Adalimumab, psoriasis, Crohn’s disease, paradoxical psoriasis.